Pelatihan Pembuatan Media Pembelajaran Flipbook Berbasis Canva yang Lebih Menarik dalam Pembelajaran Bagi Guru SMK Koperasi Yogyakarta - Rizqi Ilyasa Aghni; Vera Astuti; Arief Nurrahman (Jurnal Kemitraan Masyarakat, 2024)
Current developments require teachers to adapt to the learning process. The problem that teachers at the Yogyakarta Cooperative Vocational School still face is the development of unique and interactive learning media such as the Canva-based Flipbook learning media. Previously, the learning media that was widely used by teachers was PowerPoint, there was no alternative media that was more interactive that could be applied in the learning process, so these teachers needed Canva-based flipbook interactive media training. This training aims to make teachers skilled in developing interactive learning media using Canva-based Flipbook. Participants who took part in the training were 22 teachers. The training is filled with material delivery, discussion and practice. The results of this training activity show that: (1) the participants were satisfied with the training activities carried out, (2) the training activities were also considered effective to carry out and continue to be developed in the future, (3) the target of the product produced has also been achieved because in part Most participants were able to produce products in the form of interactive learning media using Canva-based flipbooks